The Impact of HIV/Aids on Human Capital Investment in Sub-Saharan Africa: New Evidence - Luke Chicoine; Emily Lyons; Alexia Sahue (Institute of Labor Economics (IZA), 2020)
The risk of AIDS-related mortality increased dramatically throughout the 1990s. This paper updates previous work by Fortson (2011) to examine the impact of mortality risk on human capital investment during the deadliest period of the pandemic. We combine Demographic Health Survey data from 30 countries, across 60 survey waves, to generate a sample of over 1,300,000 observations. Cohort-specific analysis using the updated sample yields new evidence that the negative relationship between HIV prevalence and schooling steepened as mortality risk increased. The reduction in schooling is largest for women, and along the extensive margin of the schooling decision. The findings indicate that the decline in human capital investment associated with the HIV/AIDS pandemic prior to the availability of treatment was larger in magnitude than previously understood, but may be reversing rapidly as access to treatment is expanded.
Keywords: I15; I25; O55; 330; HIV/AIDS; mortality risk; schooling